Taking an Early Step in Ethnobiological Research: A Proposal for Obtaining Prior and Informed Consent from Indigenous Peoples - Armando Medinaceli (Ethnobiology Letters, 2018)
Based on my own experiences from the field, in this paper I reflect on my work in Bolivia and Guatemala, collaborating with the Tsimane’ and Q’eqchi’ peoples, respectively. The aim of this reflection is to propose a set of guidelines for an early step in ethnobiological research. I understand an early step of research to be obtaining prior, informed consent of the peoples with whom we collaborate; a step I argue should be formalized and included as part of research proposals and documents (publications) resulting from the research. This guideline is offered simply as a reference for encouraging researchers to engage with the collaborating communities in a proper, ethical, and respectful way as a first step in our fieldwork. This proposed guideline, while motivating researchers to engage in this process, also encourages them to adapt and modify the guideline to the particular local situation where the planned research will take place. The proposal responds to local customs and traditions, while also following critical ethical guidelines for ethnobiological research, as well as national and international policy relevant to our field of research. It is therefore relevant to any region and community of collaborators where research takes place.